Skrjabin e il Suono-Luce - Curinga, Luisa; Rapetti, Marco (Saggi Cherubini, 2018)
Skrjabin, an eccentric figure in the music scene of the beginning of the century, has often aroused both the most heated enthusiasm and the most ferocious criticisms. However, in recent decades, important researches have been carried out in Italy and abroad, leading to a more balanced view of the man and his work. The contributions which are included in this volume come largely from the conference Svetozvuk, il 'Suono-Luce' (Cherubini Conservatory of Florence, 2015), and intend to bring a significant element to the studies on Skrjabin by addressing different and complementary themes. The resulting multifaceted kaleidoscope highlights the key role of Skrjabin in the 20th century, not only as a precursor of multimedia, but most importantly as the creator of a highly original language which would influence entire generations of musicians from different backgrounds.